2011
DOI: 10.1016/j.ultsonch.2010.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Sonolysis of ciprofloxacin in aqueous solution: Influence of operational parameters

Abstract: Ultrasonic irradiation is a promising technique for the degradation of persistent organic molecules such as pharmaceuticals in wastewater. This paper focuses on the sonolytic degradation of ciprofloxacin (CIP), a fluoroquinolone antibiotic. During a first experiment at 25°C and 544 kHz, the degradation of a 15 mg L(-1) CIP-solution showed a pseudo-first order degradation constant k(1) equal to 0.0067 ± 0.0001 min(-1) (n=3). Experiments with the addition of t-butanol as a radical scavenger showed that reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…When the concentration is 15 mg L -1 , the reported rate constant was 0.0067 min -1 , but when it is decreased to 1.5 and 0.15 mg L -1 the rate constant gets enhanced to 0.0141 and 0.024 min -1 , respectively (De Bel et al 2011). Similar results are reported for tetracycline, sulfadiazine, sulfamethazine, acetaminophen, levodopa and atenolol.…”
Section: Sonochemical Degradation Of Pharmaceutically Active Compoundssupporting
confidence: 74%
See 2 more Smart Citations
“…When the concentration is 15 mg L -1 , the reported rate constant was 0.0067 min -1 , but when it is decreased to 1.5 and 0.15 mg L -1 the rate constant gets enhanced to 0.0141 and 0.024 min -1 , respectively (De Bel et al 2011). Similar results are reported for tetracycline, sulfadiazine, sulfamethazine, acetaminophen, levodopa and atenolol.…”
Section: Sonochemical Degradation Of Pharmaceutically Active Compoundssupporting
confidence: 74%
“…The degradation of carbamazepine, ciprofloxacin, sulfadiazine, acetaminophen, levodopa, diclofenac and atenolol was reported at various frequencies (De Bel et al 2011;Isariebel et al 2009;Lastre-Acosta et al 2015;Nejumal et al 2014;Rao et al 2016). The degradation of 15 mg L -1 is found to be maximum at 544 kHz with a rate constant of 0.0067 min -1 .…”
Section: Sonochemical Degradation Of Pharmaceutically Active Compoundsmentioning
confidence: 97%
See 1 more Smart Citation
“…respectively, at the highest frequency 1,134 kHz. [30] De Bel et al [33] found that the lowest frequency, 544 kHz, proved to be the most favorable on CIP degradation. The ultrasonic frequency significantly affects sonolysis due to both the critical size and lifetime of cavitation bubbles, which consequently affects the number of cavitation bubbles, the violence of the bubble collapse and the OH• radical production.…”
Section: Influence Of Ultrasonic Frequency and Powermentioning
confidence: 99%
“…The influence of operational parameters in the sonolysis on CIP degradation and CIP initial concentration was studied by De Bel and collaborators. [33] Xiao et al [11] studied the role of matrix organic compounds on the sonolysis of CIP in aqueous solutions. The effective destruction of CIP at the frequencies of 20 and 620 kHz has been proven.…”
Section: Introductionmentioning
confidence: 99%